SAT0085 Burden of Rheumatoid Arthritis in Emerging and Developed Countries. (10th June 2014) - Moots, R.; Strand, V.; DiBonaventura, M.; Vasilescu, R.; Mahgoub, E.; Tang, B.
Abstract : Background: Whilst studies addressing the burden of rheumatoid arthritis (RA) in both developed and developing countries have been published, there is limited information available comparing these environments. Objectives: To evaluate and compare the burden of RA in developed and emerging countries. Methods: Data were analysed from the 2011 and 2012 National Health and Wellness Survey an annual cross-sectional survey conducted in 5 European Union countries (5EU: France, Germany, Italy, Spain, and UK), Japan, US, Brazil, urban China, and urban Russia. Stratified random sampling based on sex and age was used to ensure appropriate representation of the total regional adult populations. Respondents who self-reported a diagnosis of RA were compared to those without on health status (using the SF-12v2 summary scores), work impairment (using the WPAI-GH), and healthcare resource use events in the past six months using generalized linear models, controlling for demographics and health history (e.g., the Charlson comorbidity index [CCI]). Results: Prevalence of RA was comparable across 5EU, Russia, and USA (0.7% to 1.5%) and slightly lower in Brazil (0.6%). However, prevalence in urban China was highest at 2.80% and lowest in Japan at 0.10% (p<.001). RA patients in emerging countries were younger by approximately 5-10 years than those in developed countries and more likely to be employed (all p<.001). Patients in Russia and China were the most educated of all countries (p<.001), with relatively higher incomes in Brazil and China. US patients had the highest prevalence of obesity (42.4%) and, along with Russia, the greatest comorbidity burden (using the CCI; p<.001). For both developed and emerging countries, RA patients were older with a greater comorbidity burden (p<.001). Contrary to developed countries, RA patients in emerging countries had less of a gender imbalance (47.9% were male) and were more socioeconomically advantaged relative to those without RA. Across developed and emerging countries, patients with RA reported significantly worse health status, and significantly more work impairment and healthcare resource use (all p<.001; Table 1 ). Conclusions: A significant and clinically relevant health status, work impairment, and healthcare resource use burden of RA was observed across both developed and emerging countriesBased on patient characteristics of who reports a diagnosis of RA, the results suggest a disproportionate effect of healthcare access in emerging countries. Disclosure of Interest: R. Moots: None declared, V. Strand Consultant for: Pfizer, Amgen, M. DiBonaventura Employee of: Kantar Health and a paid contractor to Pfizer Inc, R. Vasilescu Employee of: Pfizer Inc, E. Mahgoub Employee of: Pfizer Inc, B. Tang Employee of: Pfizer Inc DOI: 10.1136/annrheumdis-2014-eular.4241